A comparison of four pre-processing attenuation correction methods for single photon emission computed tomography - Sayed, Inayatullah Shah; Leeman, Sidney; Betts, Mark (Meharan University of Engineering and Technology, Jamshoro, Sindh, Pakistan, 1998)
The accurate quantitation of Single Photon Emission Computed Tomography (SPECT)images is restricted due to the attention of gamma photos in patient's body. A number of approximate attenuation correction methods have been proposed to date. In this work, an attempt is made to implement four existing pre-processing (arithmetic mean-based and geometric mean based) attenuation correction methods, and to test via gathering the data by scanning a cylindrical phantom over 360 degrees. The phantom was filled with water and Tc-99m solution was uniformly distributed. An acrylic block with holes and various sizes at different interior locations with respects to wall of phantom simulating "hot" regions was used.